Game chromatic number of some convex polytope graphs - Ul Haq Bokhary, Syed Ahtsham,; Akhtar, Muhammad Shahzad, (Utilitas Mathematica, 2017)
The game chromatic number Xg is considered for some convex polytope graphs. We find the exact values for the game chromatic number of Cartesian product graph P3 □ Pn and P3 □ Cn. This extends previous results of Bartnicki et al [3] and Sia [12] on the game chromatic number of Cartesian product graphs. We have also determined the exact value for the game chromatic number of an infinite convex polytope graph Tn [9].